Program Bimbingan Untuk Mengatasi Penyelewengan Perilaku Sosial Dan Kriminal Remaja - Ananda Firdaus; Mohammad Salehudin (Program Studi Bimbingan Konseling Islam Fakultas Dakwah Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2021)
Teenagers are the nation's next generation. Adolescents are expected to have a character that is in accordance with the norms prevailing in society. However, the fact is that many crimes are committed by teenagers and originate from juvenile delinquency which is caused by various factors. Both from internal factors such as the psychological condition of adolescents themselves who are unstable due to various changes and problems that have started to emerge in their lives or external factors from an environment that is too free and has a bad impact on adolescents so that they dare to commit crimes. The guidance program is a program aimed at developing social skills and also as a medium for personal development. This research is a qualitative research that uses the literature study method by collecting various scientific articles related to the research topic. The purpose of this study was to determine whether the guidance program was able to solve the problem of social behavior deviance and crime in adolescents based on pre-existing research and it is hoped that this research can add references to academic literacy. From the various studies that have been conducted, it can be concluded that the guidance program is able to be a solution to dealing with deviant social behavior and juvenile crime. In addition, the guidance program must also be adjusted to the needs and problems faced in order to produce effective results. Key Words: guidance, teen, juvenile crime